Investigating Technology-Enhanced Item Formats Using Cognitive and Item Response Theory Approaches. Issue 2 (2nd April 2020) - Moon, Jung Aa; Sinharay, Sandip; Keehner, Madeleine; Katz, Irvin R.
Abstract : The current study examined the relationship between test-taker cognition and psychometric item properties in multiple-selection multiple-choice and grid items. In a study with content-equivalent mathematics items in alternative item formats, adult participants' tendency to respond to an item was affected by the presence of a grid and variations of answer options. The results of an item response theory analysis were consistent with the hypothesized cognitive processes in alternative item formats. The findings suggest that seemingly subtle variations of item design could substantially affect test-taker cognition and psychometric outcomes, emphasizing the need for investigating item format effects at a fine-grained level.